An Alternative Protocol for Single Zircon Dissolution with Application to (U‐Th‐Sm)/He Thermochronometry. Issue 3 (5th April 2016) - Tibari, Bouchaïb; Vacherat, Arnaud; Stab, Martin; Pik, Raphaël; Yeghicheyan, Delphine; Hild, Pascal
Abstract : Zircon (U‐Th‐Sm)/He (ZHe) thermochronometry is a powerful tool that has been widely used in geology to constrain the exhumation histories of orogens. In this study, we present an alternative protocol for dissolving zircon grains for determination of parent nuclides. This new alkali fusion procedure developed at the SARM (Service d'Analyse des Roches et des Minéraux) in Nancy, France, is fast (requiring only 2 d, including cleaning steps) and offers several advantages over conventional methods by avoiding: (i) use of HF pressure dissolution and (ii) complete removing of grains from the metal microvials. After dissolution, U, Th and Sm were measured using an ICP‐MS. We tested the new procedure on two different ZHe reference materials, the Fish Canyon Tuff and Buluk Tuff; these provided precision values for ZHe‐age estimations of 9 and 6% (1 s ), respectively. In addition, using this method, zircons from the Buluk Tuff are shown to be chemically more homogenous and more suitable for assessing the uncertainty of the entire integrated procedure. Key Points: An alternative method using alkali fusion for dissolution of single zircon grains is presented, with application to (U‐Th‐Sm)/He geochronology. Importance of mixing LiBO2 with B(OH)3 to achieve complete dissolution. Applying the new protocol, Buluk Tuff zircons yielded more precise ages than Fish Canyon Tuff zircons.